Smartwatch inertial sensors continuously monitor real-world motor fluctuations in Parkinson's disease - Powers, Rob; Etezadi-Amoli, Maryam; Arnold, Edith M; Kianian, Sara; Mance, Irida; Gibiansky, Maxsim; Trietsch, Dan; Alvarado, Alexander Singh; Kretlow, James D; Herrington, Todd M; Brillman, Salima; Huang, Nengchun; et al. (Science translational medicine, 2021)
Longitudinal, remote monitoring of motor symptoms in Parkinson's disease (PD) could enable more precise treatment decisions. We developed the Motor fluctuations Monitor for Parkinson's Disease (MM4PD), an ambulatory monitoring system that used smartwatch inertial sensors to continuously track fluctuations in resting tremor and dyskinesia. We designed and validated MM4PD in 343 participants with PD, including a longitudinal study of up to 6 months in a 225-subject cohort. MM4PD measurements correlated to clinical evaluations of tremor severity (ρ = 0.80) and mapped to expert ratings of dyskinesia presence ( < 0.001) during in-clinic tasks. MM4PD captured symptom changes in response to treatment that matched the clinician's expectations in 94% of evaluated subjects. In the remaining 6% of cases, symptom data from MM4PD identified opportunities to make improvements in pharmacologic strategy. These results demonstrate the promise of MM4PD as a tool to support patient-clinician communication, medication titration, and clinical trial design.